SISTEM PENDUKUNG KEPUTUSAN DALAM PEMILIHAN KARYAWAN TERBAIK DENGAN METODE SAW - Axel Mikaya; Zyad Rusdi; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
This Finance company works in providing financial solutions for Indonesian people. This company requires a decision support system in assessing the performance of employees in the company. The method is Simple Addictive Weighting (SAW). The SAW method is the solution to support the decision making of the system. Create a decision support system using the Simple Addictive Weighting (SAW) method to make it easier for this company to select the best employees on a certain period. Managers can set qualifications in determining the best employees. It becomes a tool in the decision support system.